Portrait of Lauren and Alyse - Unknown:::Creator::::::::::::
Photograph is a portrait, taken in the Spring of 1998, of Lauren age 9 and Alyse age 5. They are in matching outfits and are standing on either side of a small column with their forearms resting on its top. There is a large pink flower and a large blue flower behind them in the background.